Kajian Hukum Tentang Pengalihan Perkara Kredit Macet Dari Pengadilan Umum Ke Perkara Kepailitan Ditinjau Dari Asas Kepastian Hukum - Muhammad Luthfi Radian; Andi Sunandi (JURNAL HUKUM PELITA, 2022)
In the case of non-performing loans, the bank can report the debtor to the general court as an ordinary civil case, namely default in order to obtain this right. However, there are parties who want to make big profits so that their case is transferred to a bankruptcy court case. The purpose of this study is to evaluate how to test that the dispute that goes to the bankruptcy court is in accordance with the bankruptcy law, determine the billing criteria in accordance with the bankruptcy law in terms of the principle of legal certainty, and to determine debtor protection by taking into account the objectives of the bankruptcy law based on the principle of business continuity. The method used in this research is a normative juridical research method. In the library research method, the author uses secondary data, namely data obtained from library materials related to bankruptcy cases submitted to the commercial court. After the authors conducted the research, it was found that the method of examining disputes that go to the bankruptcy court is in accordance with the bankruptcy law, namely the things that must be considered by the parties to be able to file an application for bankruptcy or delay. debt payment obligations. What must be considered here are the conditions that must be met if you want to apply for PKPU or bankruptcy, including creditors must pay attention to whether the debtor is eligible to be declared bankrupt because this is regulated in Article 2 paragraph (1), namely "Debtors who have two or more creditors do not pay off at least one debt that is due and collectible, is declared bankrupt by a court decision, either at its own request or at the request of one or more creditors. The criteria for a lawsuit that is in accordance with the bankruptcy law in terms of the principle of legal certainty is that the lawsuit must be appropriate only based on the subject matter submitted by the applicant and not all types of claims are owned by the respondent. which is full to the debtor in the bankruptcy process, for example the bankruptcy principle.